Disrupt This! MOOCs and the Promises of Technology by Karen J. Head - Juravich, Nick (Radical Teacher, 2018)
Disrupt This! MOOCs and the Promises of Technology by Karen J. Head. (Boston. University Press of New England. 2017) Reviewed By Nick Juravich